Pengaruh Jenis Minyak Terhadap Karakterisasi Sifat Fisik dan Disolusi Self-Nanoemulsifying Drug Delivery System (SNEDDS) Asam Fenofibrat - Wira Noviana Suhery; Meiriza Djohari; Novia Risky Nur (LPPM Universitas Abdurrab, 2023)
The purpose of this study was to determine the effect of oil components of fenofibric acid self nanoemulsifying drug delivery systems. The investigated oils are long chain triglycerides (LCT) and medium chain triglycerides (MCT). The oils used are peanut oil (F1), castor oil (F2), virgin coconut oil (F3), and palm oil (F4). The study showed that the solubility of fenofibric acid in each oil F1 (0.57 ± 0.009 mg/ml), F2 (5.45 ± 0.17 mg/ml), F3 (0.85±0.007 mg/ml), F4 (1.04±0.03 mg/ml. The solubility of fenofibric acid in SNEDDS; F1 (27.72±0.54 mg/ml), F2 (35.50±0.96mg/ml), F3 (29.58±0.47 mg/ml), and F4 (32.14±0.44 mg/ml). The different spontaneous emulsification times were F1 (146.51 ± 2.85 seconds), F2 (37.11 ± 1.83 seconds), F3 (99.98 ± 0.63 seconds), and F4 (56.40 ± 1.71 seconds), and the results of dissolution at 60 minutes are F1 (73.66 ± 0.56%), F2 (96.52 ± 0.34%), F3 (77.87±0.81%), F4 (85.23 ± 0.98%). The type of oil can affect the characterization physical properties and dissolution of fenofibric acid SNEDDS. The best formula was shown by F2, which was a formula containing castor oil as an oil component.